The paradigm nature of today's office approaches for achieving quality outcomes in administrative office management / Kadulliah Ghazali, Noorlaila Yunus and Erne Suzila Kassim - Ghazali, Kadulliah; Yunus, Noorlaila; Kassim, Erne Suzila (2008)
In the recent years, there has been an increased in respect and responsibility given to Administrative Office Managers. This paper shall seek to explore the most challenging factors encountered by them. strategies practiced to minimize the challenges. and the benefits gained. The role of Administrative Office Managers has become even more challenging with globalization, human utilization and information technology advance issues, the need for the organizations to sustain the growth. and the need to help employees overcome resistance to the new system. A cross-sectional questionnaire survey was then conducted at several hospitality organizations in the West Malaysia. The findings suggest regardless of hotel ranking or the origin of the organization, they face and adapt similar factors. There is also a significant relationship between challenges and strategies, and the ICT investment. In addition, any deployment processes would also provide a substantial role in nurturing employees in the organizations. The study is imperative to intensify and enrich the current administrative management and hospitality management research.